2017
DOI: 10.21608/adjg.2017.5268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Smear Layer Removal and Calcium Ions Concentration in Intraradicular Dentin Treated with Apple Vinegar (SEM Study)

Abstract: Aim: This study was conducted to evaluate the smear layer removal efficiency of apple vinegar and EDTA when used as final rinse using scanning electron microscope (SEM) and to quantify the calcium content of intraradicular dentin after being treated with apple vinegar or EDTA using energy dispersive X-ray microanalyzer (EDX). Materials and methods: Fifty palatal roots of extracted human permanent maxillary molars with completely formed were selected and prepared with Universal Protaper rotary files. After usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The irrigation protocol used for the tested solutions was using 5ml for 1 minute (11) . Studies had reported that using EDTA irrigant for more than a minute resulted in erosion of dentinal tubules, which consequently reduced dentin microhardness (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…The irrigation protocol used for the tested solutions was using 5ml for 1 minute (11) . Studies had reported that using EDTA irrigant for more than a minute resulted in erosion of dentinal tubules, which consequently reduced dentin microhardness (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, coronal and middle levels have less challenge in smear layer removal in comparable with the apical level. That is due to the size of the canal in these thirds is larger than in the apical which enhance the irrigating solution efficiency (14) .…”
Section: Effect Of Root Level On Smear Layer Scoresmentioning
confidence: 99%
“…Several studies evaluated the efficacy of apple vinegar on removing smear layer and they concluded that apple vinegar was more effective when used for one minute as final rinse in removing smear layer without affecting the calcium content of intraradicular dentin compared to 17% EDTA (11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
“…The use of apple vinegar as a final irrigant has been proposed and proved better results than 17%EDTA regarding the removal of smear layer especially in the apical third (18,19) . Apple vinegar use deserves special attention due to its antimicrobial effect (20) , its biocompatibility and its cost effectiveness. It is formed of acetic, citric, formic, lactic, succinate and tartaric acids with small amounts of alcohol that results from the fermentation process.…”
Section: Introductionmentioning
confidence: 99%